2020
DOI: 10.1097/dss.0000000000002861
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Medical Spas and Physician Practices for Cosmetic Procedures: A Survey of Millennial Consumers

Abstract: strength of such relationships could be significant to one's success in the match, as these mentors will be the one vouching for the applicant's work ethic, ability to work well and get along with others, and will be writing supportive letters of recommendations-all of which were rated important by program directors in their selection process. 2,3 Interestingly, only 23.8% of successful applicants with a home fellowship program matched into their home fellowship (Table 2). This finding suggests that the bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…A study by Wang and colleagues in 2020 similarly found that most 18 to 38 year olds believed physician's offices to be safer than medical spas (69.7% vs 42.2%, p < .001). 10 Our findings also confirm that there is less physician involvement in procedures and higher complication rates of certain cosmetic procedures, including minimally invasive skin tightening and nonsurgical fat reduction, at medical spas compared with physician's offices. Less physician involvement fits with the findings presented by the ASDSA in their Position on Physician Oversight in Medical Spas that half of medical spas in the US do not have a physician on-site at all times.…”
Section: Discussionsupporting
confidence: 75%
“…A study by Wang and colleagues in 2020 similarly found that most 18 to 38 year olds believed physician's offices to be safer than medical spas (69.7% vs 42.2%, p < .001). 10 Our findings also confirm that there is less physician involvement in procedures and higher complication rates of certain cosmetic procedures, including minimally invasive skin tightening and nonsurgical fat reduction, at medical spas compared with physician's offices. Less physician involvement fits with the findings presented by the ASDSA in their Position on Physician Oversight in Medical Spas that half of medical spas in the US do not have a physician on-site at all times.…”
Section: Discussionsupporting
confidence: 75%
“…When choosing between medical spas and physician practices for body contouring, the top considerations of millennials are safety, reputation, reviews, credentials, and cost 14 . A second consumer survey reported a similar top 5 for cosmetic procedures 15 . We address these aspects below.…”
Section: Discussionmentioning
confidence: 97%
“…14 A second consumer survey reported a similar top 5 for cosmetic procedures. 15 We address these aspects below.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with consumers rating the safety of their facility as a top influential factor. Over the past few years, there has been more attention on the dangers of medical spas, which have been associated with various adverse events 3,4 5 .…”
Section: Figurementioning
confidence: 99%
“…Over the past few years, there has been more attention on the dangers of medical spas, which have been associated with various adverse events. 3,4 This may be associated with the increased incidence of providers being non-physicians, including nurses, physician assistants, and estheticians, and their overall lack of qualified physician oversight. 5 In order to promote patient safety, physicians should be aware of the dangers of medical spas and educate patients and the public accordingly.…”
mentioning
confidence: 99%